Negotiating Japanese cultural identity in the Indonesian subtitling of the anime My Happy Marriage - Haniza, Asma (Universitas Dian Nuswantoro, 2025)
This study examines the negotiation of Japanese cultural identity in the Indonesian subtitling of the anime My Happy Marriage. Employing Newmark’s (1988) cultural categories and a qualitative descriptive approach, this research analyzes culturally specific terms and their translated counterparts through a comparative method. The data were obtained from selected dialogues in the anime and their Indonesian subtitles. The findings reveal that all five categories of cultural terms—ecology, material culture, social culture, organizations and concepts, and gestures and habits—are subject to various forms of negotiation in the subtitling process. These negotiations are influenced by cultural differences and by technical constraints inherent in audiovisual translation, particularly those related to subtitle space and duration. This study contributes to audiovisual translation studies by highlighting how cultural identity is strategically negotiated rather than merely transferred in anime subtitling.